2020
DOI: 10.1371/journal.pone.0242538
|View full text |Cite
|
Sign up to set email alerts
|

Fragile heroes. The psychological impact of the COVID-19 pandemic on health-care workers in Italy

Abstract: This survey-based study aimed to explore the mental health status and psychological care needs of 933 health-care workers in Italy during the COVID-19 outbreak. Sociodemographic data, exposure to COVID-19, perception of psychological care needs, depression, anxiety, somatization, and post-traumatic symptoms were concurrently assessed. The majority of the sample (71%) suffered from somatization and 55% of distress. Female care workers experienced higher levels of anxiety (d = 0.50) and somatization symptoms (d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
112
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 64 publications
(79 reference statements)
14
112
1
3
Order By: Relevance
“…Results of descriptive statistics revealed prevalence rates of moderate to extremely severe symptoms ranging from 8 percent for depression to about 10 percent for anxiety. Participants of this study had lower levels of depression, anxiety, and stress than the prevalence reported by early studies involving healthcare workers ( Conti et al, 2020 ; Lai et al, 2020 ; Rossi et al, 2020 ). These findings could have depended on assisting patients with COVID-19 leading to an increased fear of being infected.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Results of descriptive statistics revealed prevalence rates of moderate to extremely severe symptoms ranging from 8 percent for depression to about 10 percent for anxiety. Participants of this study had lower levels of depression, anxiety, and stress than the prevalence reported by early studies involving healthcare workers ( Conti et al, 2020 ; Lai et al, 2020 ; Rossi et al, 2020 ). These findings could have depended on assisting patients with COVID-19 leading to an increased fear of being infected.…”
Section: Discussioncontrasting
confidence: 57%
“…Another study comprising a sample of 1379 Italian healthcare workers found that 49.38% expressed posttraumatic stress symptoms, 24.73% symptoms of depression, 19.80% symptoms of anxiety, and 21.90% high perceived stress ( Rossi et al, 2020 ). High psychological distress, anxiety, and depression accounted for the need for psychological support among professionals ( Conti et al, 2020 ). It was argued that promoting resilience should protect people from stress and psychopathological symptoms during the COVID-19 outbreak ( Khan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, inadequate protection, perceived stigma, and negative feedback from patients can exacerbate COVID-19-related psychological distress [ 45 , 46 ]. Also, health-care workers who perceive high level of psychological distress, need psychological support [ 47 ]. Que et al [ 45 ] suggested that psychosocial interventions should be provided in the early stages of pandemics for health-care workers who are at risk of experiencing psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, an examination of the levels of PTSD, anxiety, and depression symptoms among the study groups have revealed that dentists (who hold MD degrees), in contrast to other dental HCWs, had significantly higher PSS-SR re-experiencing, arousal, intrusions, and total scores, while dental assistants (persons without an MD degree), in contrast to other participants, had significantly higher IES-R avoidance scores. This is somewhat interesting, because nurses (which is the closest analog to dental assistant in general medicine) typically reported higher levels of symptoms and distress than doctors [ 3 , 6 , 8 , 52 ], with a few studies reporting no difference [ 53 , 54 ] and only one study reporting higher rates in doctors [ 30 ].…”
Section: Discussionmentioning
confidence: 99%